2018
DOI: 10.1088/1361-6463/aaa2f2
|View full text |Cite
|
Sign up to set email alerts
|

Ultra high-speed x-ray imaging of laser-driven shock compression using synchrotron light

Abstract: IntroductionThe properties of materials are driven to extreme conditions under high pressures, the highest of which is generated by shock compression. First described by George Gabriel Stokes in 1851 [1], 'a shock is a travelling wave front across which a discontinuous, adiabatic jump in state variables takes place'. Investigations of materials under shock compression cast light on a broad range of phenomena that are not fully understood in the areas of high-energy-density physics, earth and planetary sciences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Systems such as rechargeable batteries 41 , solidifying alloys 15,34,42,43 or evolving metallic foams 35,4446 are of special interest. Time-resolved radioscopy for very short exposure times (down to 100 ps per image) and 1 Mfps repetition rate is possible 47 , but acquisition is limited to very short periods, thus not allowing to follow longer processes continuously. Tomography naturally has been much slower than radioscopy but some proofs of concept on solid samples have shown that acquisition rates of 100 tps are feasible 48 .…”
Section: Methodsmentioning
confidence: 99%
“…Systems such as rechargeable batteries 41 , solidifying alloys 15,34,42,43 or evolving metallic foams 35,4446 are of special interest. Time-resolved radioscopy for very short exposure times (down to 100 ps per image) and 1 Mfps repetition rate is possible 47 , but acquisition is limited to very short periods, thus not allowing to follow longer processes continuously. Tomography naturally has been much slower than radioscopy but some proofs of concept on solid samples have shown that acquisition rates of 100 tps are feasible 48 .…”
Section: Methodsmentioning
confidence: 99%
“…[67,81,106] In combination with the actually achieved even higher speed of imaging, the real-time 3D diffraction imaging comes within reach. [66]…”
Section: High Speed Diffracting Imaging Of Cracksmentioning
confidence: 99%
“…The real-time observation of faster events like fracture and crack propagation in materials close to the speed of sound (up to about 4000 m s −1 e. g. in glass) needs the time structure of a synchrotron light source, combined with ultrafast imaging techniques, originally pioneered at the Advanced Photon Source (Argonne National Laboratory, USA) by Luo et al [64] Mechanically induced cracks in glass could be depicted by the so-called single-bunch phase contrast imaging at ESRF by Rack et al, with a velocity of ≈11.7 m s −1 . [65] Olbinado et al [66] used laser shock experiments to follow the compression of different materials with a MHz image rate. In polyurethane foam two fronts Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…It was important that the pulsed power fired with repeatable timing relative to the x-rays, but also that it could be manually triggered by the user. The timing scheme used here is a modification of the system used by Olbinado et al 22 A clock signal that was synchronised with the x-ray pulses was generated by the ESRF in-house developed bunch clock delay unit. This clock signal was input into a digital input/output module that could be manually triggered using the beamline computer.…”
Section: Timing and Synchronisationmentioning
confidence: 99%